Stromal immune cells expression of Siglec-15 is associated with lower T stage and better prognosis of urinary bladder cancer - Chu, Chengbiao; Fu, Yao; Yang, Jun; Fan, Xiangshan; Shi, Jiong (Frontiers in Oncology, 2024)
IntroductionSialic acid-binding immunoglobulin-like lectin 15 (Siglec-15) is a novel immune checkpoint, similar to programmed death-ligand (PD-L1), and has emerged as a potential target for cancer immunotherapy. Until recently, little was known about the expression and role of Siglec-15 in bladder cancer (BC).MethodsIn this study, we used immunohistochemical staining to assess the expression of Siglec-15 and PD-L1 in 69 primary BC samples and analyzed their relationship with clinicopathologic characters and prognosis.ResultsThe expression rates of Siglec-15 in the tumor cells, stromal immune cells, and both the tumor and stromal cells were 84.1% (58/69), 50.7% (35/69), and 44.9% (31/69), respectively. The PD-L1 expression rate was 52.2% (36/69), with a positive rate of 17.4% (12/69). PD-L1 expression was inversely correlated with Siglec-15 expression, but the statistical significance was not achieved (P = 0.072). Low stromal Siglec-15 expression was associated with advanced tumor stage (P = 0.010). PD-L1 expression was associated with tumor stage (P = 0.008) and perineural invasion (PNI) (P = 0.048). Kaplan-Meier survival curves showed that stromal Siglec-15 expression was associated with a better prognosis (P = 0.012), although it was not an independent prognostic factor after multivariate analysis (P = 0.236) .DiscussionThis study revealed a high expression rate of Siglec-15 in BC and may provide valuable insights for patient selection in future clinical trials.